2022
DOI: 10.1111/jcmm.16879
|View full text |Cite
|
Sign up to set email alerts
|

ANGPTL4 regulate glutamine metabolism and fatty acid oxidation in nonsmall cell lung cancer cells

Abstract: Lung cancer is the most common cause of cancer death in the world, with an estimated 1.6 million deaths per year. From the clinical treatment and biological characteristics, lung cancer is mainly divided into small cell lung cancer and nonsmall cell lung cancer. Approximately 85% of patients are collectively referred to as nonsmall cell lung cancer (NSCLC). Abnormal energy metabolism

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…ANGPTL4 inhibits low-density lipoprotein (LDL) activity and increases circulating triacylglycerol (TAG) levels [ 55 ]. It was also proven to increase glutamine consumption and fatty acid oxidation in non-small cell lung cancer (NSCLC) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ANGPTL4 inhibits low-density lipoprotein (LDL) activity and increases circulating triacylglycerol (TAG) levels [ 55 ]. It was also proven to increase glutamine consumption and fatty acid oxidation in non-small cell lung cancer (NSCLC) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…They were proven to function and regulate angiogenesis in the vascular system [ 11 ]. Later, ANGPTLs were reported to be widely involved in metabolic disease and tumorigenesis [ 13 , 14 , 15 , 16 , 17 ]. Specifically, ANGPTLs participate in the regulation of cell adhesion, migration, and angiogenesis in CRC [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CYP7A1 overexpression in the luteoloside intervention group was consistent with a significant increase in its enzymatic activity in the liver tissue. Angiopoietin-like protein 4 (Angptl4) is a key gene in the regulation of lipid and glucose metabolism ( 38 ), and hyperlipidemia levels were significantly reduced in Angptl4 knockout mice ( 39 ). The results of this study showed that compared with the control group, the expression of Angptl4 in liver tissues was downregulated after luteoloside intervention, but the difference was not statistically significant, indicating that Angptl4 may not be a key gene in the mechanism of luteolin lowering blood lipid.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation-mediated silencing of ANGPTL4 induces the activation of cancer-associated fibroblasts (CAFs) and help CRC transfer through the ERK pathway, enhancing its invasive ability [81]. Moreover, ANGPTL4 can participate in tumor energy metabolism in different NSCLC cells and affect cell proliferation through this process [82]. High expression of ANGPTL4 predicts adverse clinical outcomes in tumors, such as renal clear cell carcinoma, cholangiocarcinoma, melanoma, bladder cancer, and oral cancer [83][84][85][86][87].…”
Section: Discussionmentioning
confidence: 99%